Olfactory loss is a predisposing factor for depression, while olfactory enrichment is an effective treatment for depression - Leon, Michael; Woo, Cynthia C. (Frontiers in Neuroscience, 2022)
The loss of olfactory stimulation correlates well with at least 68 widely differing neurological disorders, including depression, and we raise the possibility that this relationship may be causal. That is, it seems possible that olfactory loss makes the brain vulnerable to expressing the symptoms of these neurological disorders, while daily olfactory enrichment may decrease the risk of expressing these symptoms. This situation resembles the cognitive reserve that is thought to protect people with Alzheimer’s neuropathology from expressing the functional deficit in memory through the cumulative effect of intellectual stimulation. These relationships also resemble the functional response of animal models of human neurological disorders to environmental enrichment, wherein the animals continue to have the induced neuropathology, but do not express the symptoms as they do in a standard environment with restricted sensorimotor stimulation.